2023
DOI: 10.3390/ijms24021055
|View full text |Cite
|
Sign up to set email alerts
|

Resequencing of 410 Sesame Accessions Identifies SINST1 as the Major Underlying Gene for Lignans Variation

Abstract: Sesame is a promising oilseed crop that produces specific lignans of clinical importance. Hence, a molecular description of the regulatory mechanisms of lignan biosynthesis is essential for crop improvement. Here, we resequence 410 sesame accessions and identify 5.38 and 1.16 million SNPs (single nucleotide polymorphisms) and InDels, respectively. Population genomic analyses reveal that sesame has evolved a geographic pattern categorized into northern (NC), middle (MC), and southern (SC) groups, with potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 90 publications
(128 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, lignans in sesame have been shown to be functional components with antioxidant, anti-dementia, and antihypertensive activities, and the genetic mechanisms required for lignan synthesis have been reported using QTL, GWAS, and transcriptomics in several studies ( Harada et al, 2020 ; Xu et al, 2021 ; Dossou et al, 2023 ). CYP92B14, an enzyme that converts sesamin to sesamolin and sesaminol, which was elucidated through functional characterization ( Harada et al, 2020 ), and the SiSNT1 gene located on chromosome 11, inferred through genetic mapping ( Xu et al, 2021 ; Dossou et al, 2023 ), may explain the genetic mechanisms of lignan synthesis in sesame. However, these are still poorly understood compared to other major crops.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lignans in sesame have been shown to be functional components with antioxidant, anti-dementia, and antihypertensive activities, and the genetic mechanisms required for lignan synthesis have been reported using QTL, GWAS, and transcriptomics in several studies ( Harada et al, 2020 ; Xu et al, 2021 ; Dossou et al, 2023 ). CYP92B14, an enzyme that converts sesamin to sesamolin and sesaminol, which was elucidated through functional characterization ( Harada et al, 2020 ), and the SiSNT1 gene located on chromosome 11, inferred through genetic mapping ( Xu et al, 2021 ; Dossou et al, 2023 ), may explain the genetic mechanisms of lignan synthesis in sesame. However, these are still poorly understood compared to other major crops.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the SiTPS1 gene was found to be a key regulatory gene for fatty acid biosynthesis and triacylglycerol metabolism in sesame [ 55 ]. Dossou et al identified 5.38 and 1.16 million SNPs and InDels from 410 sesame accessions, and found 17 and 72 SNP loci for the sesamin and sesamolin variation, respectively [ 56 ]. Therefore, the application of WGS in plants, along with the quick development of sequencing technology, can provide high-quality SNPs for phylogenetic and population analysis, and those results could contribute to subsequent molecular breeding, functional and evolutionary research.…”
Section: Genomicsmentioning
confidence: 99%
“…The authors managed to retrieve 4 QTLs and 41 genes, 25 of which were validated via qRT-PCR. Similarly, Dossou et al [ 14 ] characterized 410 sesame ( S. indicum ) accessions using WGR, and performed GWAS for lignan–lignin biosynthesis. The team found that SiNST1 is a major target gene for the molecular breeding of lignan content.…”
Section: Marker-guided Pre-breedingmentioning
confidence: 99%